The Threat of COVID-19 and Job Insecurity Impact on Depression and Anxiety: An Empirical Study in the USA - Obrenovic, Bojan; Du, Jianguo; Godinic, Danijela; Baslom, Mohammed Majdy M; Tsoy, Diana (Frontiers in Psychology, 2021)
As the COVID-19 pandemic causes a general concern regarding overall mental health of employees worldwide, policymakers across nations are taking precautions for curtailing and scaling down dispersion of the coronavirus. In this study we conceptualized a framework capturing recurring troublesome elements of mental states such as depression and general anxiety, assessing them by applying standard clinical inventory. The study explores the extent to which danger control and fear control under the EPPM threat impact job insecurity, with uncertainty phenomenon causing afflicting effect on experiential nature of depression heightened by anxiety. With the aim to explore the job insecurity relationship with anxiety and depression and measure the impact of EPPM threat, an empirical study was conducted in the USA on a sample of 347 white-collar employees. Demographic data, EPPM threat, job insecurity, anxiety, and depression data were collected via a standardized questionnaire during the COVID-19 pandemic. The questionnaire consisting of multiitem scales was distributed online. All scale items were evaluated on a 5-point Likert scale. SEM software AMOS version 23 was used to perform Confirmatory Factor Analysis with Maximum likelihood estimation. In the structural model, relationships between the Threat of COVID-19, Job insecurity, Anxiety and Depression were assessed. The study's findings suggest that job insecurity has a significant impact on depression and anxiety, whereas the threat of COVID-19 has significant impact on depression. Mediating effects of job insecurity and the EPPM threat impact on anxiety were not established in the study. The study contributes to the apprehension of the repercussions of major environmental disruptions on normal human functioning, and it investigates the effects of self-reported protective behaviours to risk perception. The paper also explains the underlying mechanisms of coping behavior as possible antecedents to mental disorders. When subject to stressful events, heighten psychological arousal causes physical and psychological challenges of affected employees to manifest as behavioural issues.